Non-fungible tokens and consumer behavior: A systematic literature review and research agenda - Griffiths , P; Nuno Fernades Crespo; Costa, C. (International Journal of Consumer Studies, 2025)
Non-fungible tokens (NFTs) are digital artifacts built on blockchain technology that have achieved notoriety for their rapid consumer adoption, technical sophistication, and dramatic price swings. This paper synthesizes contemporary academic research on NFT consumer behavior to better understand the current state of the field, to explore its focus and quality, and to identify the authors and subjects that are driving the research. Applying the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) protocol and using an ACO-TCM framework systematic review of literature, this study of 53 curated articles organizes the existing body of research on NFT consumer behavior to identify current themes and gaps in the academic literature, finding ample opportunities for further research. Finally, this paper proposes areas for further study based on the emerging opportunities in research streams, both in depth and in breadth, concerning NFT consumer behavior.